Major adverse cardiovascular events: analysis of diabetics with coronary syndrome on prior use of acetylsalicylic acid - Edna Rodrigues de Melo; Fernanda Ribeiro Carvalho (Universidade de Pernambuco, 2022)
Objective: To investigate diabetic patients admitted toa private hospital with acute coronary syndrome who had previously used acetylsalicylic acid to prevent major adverse cardiovascular events. Methodology: It is a descriptive study with a quantitative approach. Data collection was extracted from the chest pain protocol of a private institution in Rio de Janeiro in the local emergency room with geriatric audiences, between the year 2013 and June 2019 we counted 312 diabetic patients with acute coronary syndrome. Results: Of the 312 diabetic patients, 151 used acetylsalicylic acid early and 161 did not use ASA previously. Of these, respectively, 5 had a diagnosis of infarction with supra and 22of the diabetic patients who did not use ASA had a diagnosis of AMI with supra in the emergency room. Conclusion: Aspirin use plays a crucial role in preventing major adverse cardiovascular events. Finally, the previous use of ASA remains as an immediate treatment for individuals with ACS, even before or after hospital admission.